2009
DOI: 10.1111/j.1600-0722.2009.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral bacterial adhesion forces to biomaterial surfaces constituting the bracket–adhesive–enamel junction in orthodontic treatment

Abstract: Bacterial adhesion to biomaterial surfaces constituting the bracket-adhesive-enamel junction represents a growing problem in orthodontics, because bacteria can adversely affect treatment by causing demineralization of the enamel surface around the brackets. It is important to know the forces with which bacteria adhere to the surfaces of these junction materials, as the strength of these forces will determine how easy it will be to remove the bacteria. We compared the adhesion forces of five initially colonizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 38 publications
4
46
0
Order By: Relevance
“…However, this relationship is not a linear correlation since the chemical composition of the surface tends to govern the interaction which depends on both the chemistry of the solid and immersion liquid and additionally the type of bacteria and growing media. This has resulted in conflicting reports with reports suggesting that materials with low SFE result in less bacterial adherence [23,40]; whilst other contrary reports found that bacterial adhesion decreased with increasing surface energy of substrates [41][42][43]. The addition of EgMA monomer containing a substituted aromatic ring into the formulation significantly increased the hydrophobicity leading to an increase of the surface contact angle and reducing the SFE values from 54.3 mN/ m for the control, to 47.7 and 44.8 mN/ m for composites containing 5% and 10% EgMA respectively.…”
Section: Discussionmentioning
confidence: 43%
“…However, this relationship is not a linear correlation since the chemical composition of the surface tends to govern the interaction which depends on both the chemistry of the solid and immersion liquid and additionally the type of bacteria and growing media. This has resulted in conflicting reports with reports suggesting that materials with low SFE result in less bacterial adherence [23,40]; whilst other contrary reports found that bacterial adhesion decreased with increasing surface energy of substrates [41][42][43]. The addition of EgMA monomer containing a substituted aromatic ring into the formulation significantly increased the hydrophobicity leading to an increase of the surface contact angle and reducing the SFE values from 54.3 mN/ m for the control, to 47.7 and 44.8 mN/ m for composites containing 5% and 10% EgMA respectively.…”
Section: Discussionmentioning
confidence: 43%
“…Atomic force microscopy has pointed out that bacterial adhesion forces to different materials used in orthodontics, including stainless steel, differ from the ones exerted by enamel surfaces in a strain-specific fashion. 35 Accordingly this explains 36 why biofilms on different materials have a different bacterial composition, including the enamel and stainless steel surfaces as involved here. Furthermore, the biofilm taken from retention wires will be more mature than biofilm taken from smooth enamel surfaces, as more biofilm will be left-behind after brushing on retention wires than on smooth enamel surfaces on which biofilm has to develop newly after each brushing.…”
Section: Discussionmentioning
confidence: 95%
“…It is amazing how such small differences in bacterial adhesion forces can select strains from saliva to become members of the adhering microbiome. Earlier, it had already been found that initial colonizers of dental hard surfaces possess adhesion forces to saliva-coated enamel that are only 0.1 nN stronger than those of later-colonizing, more cariogenic strains (Mei et al, 2009). With respect to Staphylococcus aureus strains, a difference in adhesion force of 0.28 nN appears to dictate whether or not a strain can invade mammalian cells (Yongsunthon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%